Avaliação do papel dos receptores 5-ht2 da substância cinzenta periaquedutal de camundongos submetidos ao labirinto em cruz elevado - Souza, Vanessa Nunes de (Universidade Federal de São Carlos, 2008)
It is widely acknowledged that the indoleamine neurotransmitter serotonin (5-HT) plays a dual role in the regulation of anxiety, a role that in part depends upon neuroanatomical locus of action. Thus, whereas stimulation of 5-HT1A or 5-HT2 receptors in the limbic forebrain (amygdala, hippocampus) enhances anxiety-like responding in rodents, activation of corresponding receptor populations in the midbrain periaqueductal grey (PAG) more often than not reduces anxiety-like behavior. The present study specifically concerns the anxietymodulating influence of 5-HT2 receptors within the mouse PAG. Experiment 1 assessed the effects of intra-PAG infusions of the 5-HT2B/2C receptor agonist mCPP (0, 0.03, 0.1 or 0.3 nmol/0.1 µl) on the behavior of mice exposed to the elevated plus-maze. Experiment 2 assessed the effects of intra-PAG infusions of the preferential 5-HT2A/2C receptor antagonist ketanserin (0 or 10 nmol/0.1 µl), on the behaviour of mice exposed to the elevated plus-maze. As mCPP acts preferentially at 5-HT2B and 5-HT2C receptors, Experiment 3 investigated its effects in animals pretreated with ketanserin. The test sessions were videotaped and subsequently scored for anxiety-like behaviour (e.g. percentage of open arm entries and percentage of open arm time) as well as general locomotor activity (closed arm entries). The results of Experiment 1 showed that mCPP microinfusions (0.03 and 0.1 nmol) into the PAG of mice decreased behavioural indices of anxiety without significantly altering general activity measures. Results of experiment 2 showed that intra-PAG infusions of ketanserin (10 nmol) did not alter conventional indices of anxiety, nor locomotor activity. In Experiment 3, the anxiolytic-like profile of intra-PAG mCPP (0.03 nmol) was substantially attenuated by intra-PAG pretreatment with an intrinsically-inactive dose of the preferential 5-HT2A/2C receptor antagonist, ketanserin (10 nmol). Together, these data suggest that 5HT2C receptor populations within the midbrain PAG play an inhibitory role in plus-maze anxiety in mice.
Keywords: Psicofarmacologia; Ansiedade; Labirinto em cruz elevado; Camundongo; Receptores 5-ht2; Substância cinzenta periaquedutal; CIENCIAS BIOLOGICAS::FISIOLOGIA